The Effect of Circuit and Interval Training on Maximum Oxygen Volume (VO2max) in Professional Futsal Athletes - Mahmud Yunus; Slamet Raharjo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Futsal is one of the most popular sports in society and has attracted more and more fans all over the world. There are more than 12 million people spread over 100 countries who have played futsal. Futsal is played by one goalkeeper and four field players with a duration of two rounds of 2 × 20 minutes. Therefore, every player must have a good physical condition to play optimally. Maximum oxygen volume (VO2max) is an indicator that can be used to determine the status of a person's physical condition. This study aims to compare the effect of circuit and interval training on VO2max in professional futsal athletes. The method used in this research is quantitative with a two-group pretest-posttest design. A total of 24 teenage boys, aged 16-21 years with a body mass index (BMI) of 19 kg/m2 – 23 kg/m2 participated in this study. Interval training and circuit training are carried out with an intensity of 80% – 90% HRmax, a frequency of 3 times/week for 8 weeks. VO2max was measured using the 20-M Shuttle Run Test with two measurements, namely pre-training and post-training. The results showed the average pre-training VO2max between interval training group (ITG) vs. circuit training group (CTG) (37.82±2.39 vs. 38.56±2.79 mL/kg/min (p ? 0.05)), post-training ITG vs. CTG (39.69±2.51 vs. 42.88±2.71 mL/kg/min (p ? 0.001)), delta ITG vs. CTG (1.88±0.99 vs. 4.32±1.09 mL/kg/min (p ? 0.001)). Based on our results, we show that interval training and circuit training increase VO2max. However, circuit training is more effective in increasing VO2max compared to interval training on professional futsal athletes.